Harmonization of the Turkish banking regulation to the European Union, with special emphasis to risk management - Ersoy, İmre S. (My University, 2003)
The study aims to analyze the international regulatory and supervisory framework for risk management that emerged as a response to the banking crises, to define the regulatory architecture in the EU accordingly, and to reflect the implications of the harmonization of Banking Regulation of Turkey with the EU, in terms of preventing possible future systemic banking crises in Turkey. The banking crises in the developing countries like Turkey are systemic banking crises and erupt when the existing institutional problems couple with macroeconomic shocks of particularly interest rate and exchange rate volatilities. In the developed countries, like EU member states, however, the problems are more restricted to individual bank problems or significant incidences due mainly to microeconomic credit, market and operational risks. The international regulatory and supervisory framework of BIS for risk management, which is extended to EU with parallel initiatives, increases the capital adequacy levels of the developing country banks. However, as the Basel framework covers the risk exposures of developed country banks, and as EU does not adapt the Basel initiatives that concern the developing countries, the harmonization of the regulatory and supervisory framework of Turkey with the EU does not immunize the Turkish Banking System from new crises. Turkey should adapt the International Risk Management Regulation rather than precisely adopting, and implement the initiatives for Effective Supervision and Interest Rate Risk Management. Turkish banks should apply higher standards than required by Basel I, prepare them to Basel II, and besides Basel frameworks, also apply the ALM Techniques to protect themselves from their own risk exposures to crises.

Bu çalışma, bankacılık krizlerini önlemek amacıyla risk yönetimi konusunda geliştirilen uluslararası yasal ve denetim çerçevesini, bu çerçevenin Avrupa Birliği uzantısını ve Türk bankacılık sisteminin Avrupa Birliği bankacılık sistemi ile uyumlaştırılmasının Türk bankacılık sistemini yeni muhtemel krizlerden ne ölçüde koruyabileceğini analiz etmeyi amaçlamaktadır. Türkiye gibi gelişmekte olan ülkelerde bankacılık krizleri sistemik krizlerdir ve varolan kurumsal problemler, özellikle faiz ve kur volatilitesi gibi makroekonomik şoklarla birleşince ortaya çıkar. Avrupa Birliği üyeleri gibi gelişmiş ülkelerde ise bankacılık problemleri bireysel veya dar kapsamlı problemlerdir ve kredi, piyasa ve operasyonel riskler gibi mikroekonomik risklerden kaynaklanır. Avrupa Birliğinde de paralel yasal düzenlemelerle uygulanan BIS'in uluslararası yasal ve denetim çerçevesinin, gelişmekte olan ülkelerin sermayelerini arttırmak yönünde olumlu etkisi olmaktadır. Ancak, Basel düzenlemeleri, gelişmiş ülke bankalarının maruz oldukları risklere karşı bankaları koruyan yapıda olduğu ve Avrupa Birliği gelişmekte olan ülkelerle ilgili yasal düzenlemeleri kendisine uyarlamadığı için, Türk bankacılık düzenlemelerinin Avrupa Birliği ile uyumlaştırılması, Türk Bankacılık Sistemini yeni krizlere karşı koruyamıyacaktır. Türkiye, Uluslararası Risk Yönetim Mevzuatını olduğu gibi almak yerine kendisine uyarlamalı ve Etkin Denetim, Faiz Risk Yönetimi konularındaki düzenlemeleri uygulamaya başlamalıdır. Türk bankaları, Basel I'in gerektirdiğinden daha yüksek standartlar uygulamalı, Basel II'ye hazırlanmalı ve Basel yasal düzenlemeleri yanısıra Aktif/ Pasif Yönetimi tekniklerini de uygulayarak kendilerini maruz oldukları kriz risklerine karşı korumalıdırlar.
Keywords: Avrupa Topluluğu; Bankalar ve Bankacılık; Risk Yönetimi